HUBUNGAN KELINCAHAN DENGAN KEMAMPUAN MENGGIRING BOLA DALAM PERMAINAN SEPAKBOLA PADA TIM SEPAKBOLA SMP NEGERI 7 BUKIT BATU - Sabarudin, Sabarudin; Slamet, Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, Problems in this study originated from the observation of the author encountered in the field, that student still less nimble in dribbling. Movement dribble still less flexible and not infrequently the ball regardless of foot control students. Dribbling technique is still not quite right. Issues that are taken in this study is whether there is a relationship agility with the ability to dribble in the game of football on the football team SMP Negeri 7 Bukit Batu. The purpose of this study was to determine the relationship of agility with the ability to dribble in the game of football on the football team SMP Negeri 7 Bukit Batu. The method used in this study is a test and measurement techniques to analyze the correlation Further data using product moment correlation analysis technique. The population in this study were students who entered in the Junior High School soccer team 7 Bukit Batu, amounting to 24 people. The sampling technique used is saturated sample, where all the population sampled so that the sample in this study amounted to 24 people. From the measurement results of the test product moment correlation of data obtained rhitung = 0.721> rtabel = 0.404 then known distribution value amounted to 4.88 thitung> table = 1.717 thus rejected Ha Ho accepted. Conclusion The hypothesis is accepted at significance level α = 0.05 in other words the presence of a relationship agility with the ability to dribble in the game of football on the football team SMP Negeri 7 Bukit Batu.Keywords : Agility, Dribbling, Football